Ewolucja marketingu politycznego w percepcji wyborców - Churska-Nowak, Karolina; Fojutowski, Łukasz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The purpose of this paper is to demonstrate how political marketing is perceived by voters. The paper poses research questions and hypotheses with respect to the potential positive and negative consequences of the development of marketing-oriented politics. The empirical part confronts those assumptions with the reality. It presents the results of research into the perception of political marketing by university students in Poznań.